The ‘universal library’ returns in digital form (Libellarium: journal for research in the field of information and related sciences, 2009)
This paper begins with two contemporary technological developments both of which present a serious challenge to the dominance in literature and learning of the book in its codex form. While their earlier manifestations were not commercially successful, the most recent e-book readers (portable technological contraptions that have the capacity to store thousands of books that can be read electronically) have been praised not only for their functionality but also for their aesthetic appeal. A relateddevelopment has been the growth of large-scale digital libraries, the most prominent of which is the Google Books Library Project, launched in 2004 and now committed to the digitisation of around 15 million volumes or 4.5 billion pages in the following six years from some of the world’s leading academic libraries.The purpose of this paper is to explore these developments within the context of ancient and Enlightenment ideas about the ‘universal library’ which assert that the construction of such an institution is the most effective way of promoting universal knowledge. Rather than employing a kind of technological determinism that renders these technologies as merely points along an inexorable continuum of progress, it will be argued that they are the latest manifestation of an idea that long pre-dated digital technology. Over two millennia ago, the Ptolemies attempted to collect the entire corpus of literature in the Greek language as well as significant works in other languages. Many have argued that the institution that held these huge collections, the library at Alexandria, was effectively the world’s first universal library. Even though this library was eventually destroyed, the idea of universalism survived and flourished again during the European Enlightenment, through Diderot’s Encyclopédie project and the construction of national libraries and archives. Latterly, the creation of the World Wide Web is conceived of by some as the apotheosis of the universalism of knowledge.Not everyone is convinced, though, that the attainment of universal knowledge is possible. And, ironically, the most powerful arguments against universalism emanate from a medium whose existential status is most threatened by this idea and its accompanying technologies: the codex book. Despite our technological sophistication, it seems that literature is still able to give us much richer insights into the nature of contemporary society than other forms of media. This paper will illustrate this through the writings of Jorge Luis Borges, Jonathan Swift, Jean Paul Sartre, Washington Irving and Gustave Flaubert, who in their various ways demonstrate the epistemological impossibility of obtaining total knowledge in any intellectual discipline, parody the insane search for it and muse on the tension between canonicity and universalism. These issues are particularly pertinent in an age where the virtualization of text has seemingly rendered obsolete some of the practical obstacles to the universal library and offer a sophisticated rejoinder to those cyber-utopians who have heralded the imminent arrival of universal knowledge via the World Wide Web
Keywords: the Enlightenment; universal library; World Wide Web; universal knowledge; canonicity; archives; positivism